2020
DOI: 10.2109/jcersj2.19156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of annealing temperature on photovoltaic properties of lead-free (CH<sub>3</sub>NH<sub>3</sub>)<sub>3</sub>Bi<sub>2</sub>I<sub>9</sub> solar cells

Abstract: Effects of annealing temperature on photovoltaic properties of lead-free (CH 3 NH 3 ) 3 Bi 2 I 9 solar cells were investigated. The (CH 3 NH 3 ) 3 Bi 2 I 9 photovoltaic cells were fabricated by a hot air blow-assisted spin-coating method. The spin-coated (CH 3 NH 3 ) 3 Bi 2 I 9 photoactive layers were annealed at temperatures of 100150 °C. Current densityvoltage characteristics of the (CH 3 NH 3 ) 3 Bi 2 I 9 photovoltaic cells showed that conversion efficiency increased with increasing annealing temperature. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our explanation agrees well with Mariyappan et al, who reported that the peaks intensity and the crystallinity corresponding to CB treated CBI perovskite were improved [3]. Furthermore, we calculate the crystallites size, D, of HPeSCs using the Scherrer equation [24] and it increases as CBI composition increased as shown in Figure 2(a). Likewise, the thickness of HPeSCs is increased as well as shown in Figure 2(b) and (c).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our explanation agrees well with Mariyappan et al, who reported that the peaks intensity and the crystallinity corresponding to CB treated CBI perovskite were improved [3]. Furthermore, we calculate the crystallites size, D, of HPeSCs using the Scherrer equation [24] and it increases as CBI composition increased as shown in Figure 2(a). Likewise, the thickness of HPeSCs is increased as well as shown in Figure 2(b) and (c).…”
Section: Resultssupporting
confidence: 88%
“…It can be observed that the main-phase peak of CBI at 25.14 o (00-6) 18) is increased in intensity as increasing the CBI composition except for x=0, which no CBI peak is observed. One peak of TiO 2 is observed at 25.37 o [23] and three of FTO peaks are observed at 26.82 o [24],…”
Section: Resultsmentioning
confidence: 96%
“…Ataei et al [34], in 2021, fabricated MBI PeSCs by using the spin-coating method, but they suffered a non-uniformity surface morphology of MBI films, and the efficiency of the device was only 0.8%. While Shirahata et al [44] in 2020, employed the hot air blow technique. The researchers obtained highquality and rapidly crystallized MBI films; however, the morphology of the films was not uniform; it was rougher and not compact, and the efficiency was only 0.06% [44].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…While Shirahata et al [44] in 2020, employed the hot air blow technique. The researchers obtained highquality and rapidly crystallized MBI films; however, the morphology of the films was not uniform; it was rougher and not compact, and the efficiency was only 0.06% [44]. In the same year, Momblona et al [5] fabricated MBI films through the thermal co-evaporation method and obtained an efficiency of 0.01%; however, the fabricated films were not smooth and had a rougher surface even after employing a complicated process.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%